Faktor-Faktor yang Berhubungan dengan Kepatuhan Minum Obat Pasien Tuberkolusis Paru - Utari Ulandari; Agus Ramon; Eva Oktavidiati; Nopia Wati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify factors associated with medication adherence among pulmonary TB patients in the Telaga Dewa Public Health Center (Puskesmas) service area in Bengkulu City. This is a quantitative study with a cross-sectional design, conducted in May–June 2025. The sample size was 45 respondents, selected using random sampling from a total of 80 patients. Data were collected using a questionnaire and analyzed using the chi-square test. The results showed a significant association between knowledge (p=1,000), attitude (p=0.01), and family support (p=0.04) with medication adherence among pulmonary TB patients. The conclusion of this study is that the level of knowledge, positive attitude, and strong family support play an important role in improving patient compliance with treatment. Keywords: Attitude, Knowledge, Support, Tuberculosis